Disability and accessibility in the library and information science literature: A content analysis - Hill, Heather (Library & information science research, 2013)
The library profession is a strong and vocal proponent of increased information access for people with disabilities. With the discipline's longstanding interest in the subject of services to people with disabilities, questions arise about how the profession perceives the phenomenon. How is library and information science (LIS), as a discipline, conceptualizing disability and accessibility? A content analysis of the LIS literature was conducted to examine this question. The literature provides a fertile ground for study as it reflects the profession's approaches to, and perceptions of, a topic. This research identifies the major issues and trends in the research about accessibility and disability in the LIS literature throughout a 10-year period, 2000–2010. The strongest theme in the literature is accessibility as it relates to web, database, and software, while the prevailing disability of focus is visual disabilities. The overall environment emphasizes technology more than attitudinal aspects associated with disabilities. The research could benefit from increased direct participation of people with disabilities. ► Content analysis was performed on accessibility and disability in the LIS literature. ► Coded themes included disability types and participation of those with disabilities. ► The literature focuses on electronic accessibility and visual disabilities. ► People with disabilities are rarely active participants in the literature.